Analysis of existent processes and devices of bioscrubbing gas emissions - Шестопалов, Олексій Валерійович; Пітак, Інна В’ячеславівна (Technology audit and production reserves, 2014)
The paper analyzes the processes and devices of treatment and deodorization of air-gas emissions. The main purpose of the research is to synthesize and classify the processes, forming the basis of the biotechnological detoxification of emissions. The analysis has revealed disadvantages of the existent thermal, reagent and physicochemical methods of treatment and deodorization of emissions. Benefits of using the biological degradation of industrial toxicants are outlined. It was shown that the methods of biological treatment of gaseous contaminants, in which toxic substances are decomposed into simple ones, are versatile, have low operating costs and do not cause secondary air contamination. The mass transfer processes, occurring during the migration of contaminants from the gas phase to the cells of bacterial associations are highlighted. The results of the experiments using different bacterial associations have shown the effectiveness and industrial applicability of the biological method of treatment from organic hydrocarbons, halogen compounds, as well as sulfur and nitrogen compounds. The research results can be applied in the development of environmentally compatible biotechnologies of treating air-gas emissions of anthropogenic origin.